FORCED DETENTION OF PERSONS WITH MENTAL DISORDERS IN THE SERBIAN CRIMINAL LAW - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In this article the author deals with an issue of forced detention of persons with mental disorders in the Serbian criminal law. The author provides analysis of this issue as well as of the relationship between criminal law, misdemeanor law and the Law on Protection of Persons with Mental Disorders, and points out that provisions of this Law can only conditionally, and with reservation, be considered as part of the criminal law. In the first part of the article the author discuses the subject matter of his research and lists and explains the aims he wishes to attain by this article. In the second, third, and fourth part of the article the author examines individual forms of forced detention in the Serbian law, which covers detention prescribed by criminal law, misdemeanor law, as well as detention regulated by provisions of the Law on Protection of Persons with Mental Disorders. In the last part of the article the author provides a detail summary of the issues he covered in the article, followed by his evaluation and judgment on the scope and correlation between legal norms that regulate this subject matter in different areas of the law, and finally gives certain proposals that would put persons with mental disorders in a more favorable legal position.